PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERMUATAN BUDAYA LOKAL CANDI BADUT MALANG PADA MATERI BANGUN DATAR - Victoriana Ohoiledwarin; Dian Fitri Argarini; Choirul Kurniawan (Universitas Teknokrat Indonesia, 2026)
Learning plane geometry in junior high school still faces several challenges, particularly students’ limited spatial visualization skills and the lack of interactive and contextual learning media. This study aimed to develop an interactive PowerPoint-based learning media integrating the local culture of Badut Temple Malang and to determine its validity, effectiveness, and practicality. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were seventh-grade students of SMP PGRI 08 Malang, while media and material experts were involved in the validation process. Data were collected through validation sheets, learning achievement tests, and student response questionnaires. The results revealed that the developed media obtained a validity score of 76% from the media expert, categorized as feasible, and 99% from the material expert, categorized as highly feasible. The effectiveness test yielded a score of 88%, categorized as effective, while the practicality assessment based on student responses reached 93%, categorized as highly practical. The novelty of this study lies in integrating the geometric elements of Badut Temple Malang into an interactive PowerPoint-based learning media as a contextual approach to teaching plane geometry. Therefore, the developed media meets the criteria of validity, effectiveness, and practicality, making it suitable for mathematics learning and capable of providing a more contextual and meaningful learning experience.